Analisis Transaksi Akad Salam Dalam Jual Beli Online - Aly Akbar (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
Based on the previous discussion, and referring to the results of the research that has been done, it can be concluded the following points: The greeting contract scheme in buying and selling online there is muslam (buyer), muslam ilaih (seller), muslam fihi (object of goods) and also sighat ( consent and qabul); The contract of greeting in buying and selling online, has fulfilled the rules and legal requirements that apply in the law of fiqh, and is in accordance with the DSN MUI fatwa in 2000. Looking at the process and scheme of the agreement to sell online this is a permissible form; The mechanism in the transaction of the contract to buy and sell online makes it easy for consumers to make transactions online.